An Evaluation of the Training Program at the Implementation Unit Work Training Center - Widayanto, Luthfi Dhimas; Soeharto, Soeharto; Sudira, Putu; Daryono, Rihab Wit; Nurtanto, Muhammad (Journal of Education Research and Evaluation, 2021)
This research aims to evaluate the achievement of the implementation of training programs at UPT BLK Surabaya and to provide recommendations for the next training program. This research is evaluation research using the CIPPO (context, input, process, product, and outcome) model. The research instrument is a questionnaire validated through expert judgment, and given to two groups of respondents: the training participants and instructors. The research respondents were 199 consisting of 180 training participants, 19 instructors. The research findings are as follows. (1) The context aspect, which is the suitability of the program with the objectives of the institution, the needs of the community and industry, was stated good by the participants and very good by instructors and supported by the completeness of legal basic documents and the characteristics of the training program. (2) The input aspect, which is infrastructure, selection process, instructors competence, curriculum, and funds were stated good by the participants and very good by instructors. (3) The process aspects, which are planning, implementation, and supervision, are in accordance with the SOP applied by the government. The implementation of the training program was stated good by the participants and very good the instructors. (4) The product aspect, which is the competence of the participants, was stated very good by participants and instructors. (5) In the aspect of outcome, the percentage of the absorption rate of graduates in the business sector and industrial sector is 37%. The recommendation to the aspect of infrastructure is to increase the number and cleanliness of bathrooms.